Effects of provenance variation on nursery development of Santalum album L. in Himachal Pradesh - Ruchi, T; Tara, G; Gupta, R K; Kumari, Anita; Dushyant, K S; Manisha, T; Dhirender, K; Sahil, T (Plant Science Today, 2026)
Provenance variation in Santalum album L. arises from both genetic and environmental influences, highlighting the need to identify superior seed sources for enhanced germination and growth. This study evaluated seeds from six sources across three forest divisions in Himachal Pradesh, viz., Changer (S1), Kosariyan (S2) and Samoh (S3) in Bilaspur; Hiranagar (S4) in Hamirpur and Jwalamukhi (S5) and Sadwan (S6) in Kangra. One-way analysis of variance (ANOVA) under a randomized block design (RBD) was applied to analyse seed weight and diameter, while two-way ANOVA (RBD) was used to assess seed germination and seedling growth parameters. Kosariyan (S2) had the largest seed diameter (6.99 mm) and the highest 100-seed weight (14.58 g). Seeds with the largest sizes generally exhibited higher weights; however, their germination percentage was significantly lower compared to seeds with smaller diameters, except for Kosariyan (S2). Seeds sown in April 2020 exhibited better germination (68.52 %) than those sown in May (47.61 %). Kosariyan (S2) achieved the highest germination percentage (66.68 %) and energy (34.42 %). In vitro germination on Murashige and Skoog (MS) medium was higher compared to autoclaved sand. Sadwan (S5) excelled in seedling growth, with half-sib seedlings achieving the maximum seedling height (21.62 cm), collar diameter (3.2 mm), leaf length (6.32 cm) and leaf width (2.3 cm) at one year of age. Seedling height demonstrated high heritability and genetic gain, making it a valuable trait for selection. The findings highlight significant provenance variation, with Kosariyan (S2) and Jwalamukhi (S5) emerging as superior for germination and growth performance, respectively. These findings underscore the need to identify and utilize optimal seed sources to promote sustainable and productive cultivation of S. album.